Teori Atribusi: Memahami Hubungan Kualitas Layanan, Pemahaman Perpajakan, Implementasi Sanksi dan Kepatuhan Pajak - Wardani, Siti; Kurniawan, Rudy; Haryono, Haryono (Magister Akuntansi Universitas Pancasila, 2024)
Tax is a mandatory contribution made by citizens to the government in accordance with the provisions of the law, which is the largest source of income for the state. However, in Indonesia, there are still problems in tax activities, including low tax ratios and low levels of tax compliance. This research aims to investigate the influence of service quality, understanding of taxation, and implementation of sanctions on tax compliance in West Kalimantan Province. The research method used is quantitative with a multiple linear regression analysis approach using the help of the IBM SPSS program in processing the data. Primary data was collected through questionnaires distributed to people who have a Taxpayer Identification Number (NPWP) and regularly report Tax Returns (SPT) to the tax authority. The research results show that service quality does not have a significant effect on tax compliance, while understanding taxation and implementation of sanctions significantly influence tax compliance. The level of tax compliance can be increased by improving service quality, understanding of taxation, and the effectiveness of implementing sanctions. These findings provide valuable insights for tax authorities in improving tax compliance and increasing overall tax revenue.